Kekuatan Pembuktian Laporan Hasil Analisis Pusat Pelaporan Dan Analisis Transaksi Keuangan (PPATK) Dalam Penanganan Tindak Pidana Pencucian Uang - I Nengah Nuarta; Ketut Krisna Hari Bagaskara P (Jurnal Preferensi Hukum, 2025)
The Financial Transaction Reports and Analysis Center (PPATK) in carrying out its duties to combat money laundering, conducts the stages of analysis and examination of reports or information related to financial transactions. In an effort to accelerate the prevention of money laundering, the President has directed the optimization of the use of the Analysis Results Reports of the Financial Transaction Reports and Analysis Center. Based on this background, the researcher is interested in examining the following matters: 1. What is the authority of the Financial Transaction Reports and Analysis Center (PPATK) in proving money laundering crimes currently? 2. How will the authority of the Financial Transaction Reports and Analysis Center (PPATK) to prove money laundering crimes be reformulated in the future? This research is a normative legal research. This approach is carried out by presenting the collected legal materials, which are then analyzed in a manner consistent with their nature, namely descriptively, evaluatively, and prescriptively. The PPATK's authority to prove money laundering crimes is currently regulated under several laws and regulations in Indonesia, including Law Number 8 of 2010, Presidential Regulation Number 50 of 2011 concerning Procedures for Implementing the Authority of the Financial Transaction Reports and Analysis Center, and Presidential Instruction Number 2 of 2017 concerning Optimizing the Utilization of Analysis Reports and Examination Reports from the Reporting Center. Reformulation of PPATK's evidentiary authority regarding money laundering in the future by interpreting the position of PPATK’s Analysis Results Reports (LHA) as documentary or electronic evidence.